VERNACULARIZATION ASPECTS IN BISRI MUSTOFA'S AL-IBRIZ TAFSIR - Abidin, Ahmad Zainal; Thoriqul Aziz; Rizqa Ahmadi (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2022)
This study aims to explain how aspects and forms of vernacularization in Tafsir al-Ibriz li Ma'rīfati Tafsīr Qur'ān al-'Azīz by Bisri Mustofa. As an interpretation still being studied from the beginning until today, especially in pesantren in Java, Tafsir al-Ibriz occupies an important position in the community. This interpretation, completed in 1964, shows the form and aspects of the Qur'an's localization in the context of Javanese society. Based on library research and the descriptive-analytical method, this article indicates that Bisri Mustofa's vernacularization can be seen from two aspects: firstly, in terms of language or terms. Generally, the language used in the interpretation of al-Ibriz is the Javanese language and some terms for laypeople. Therefore, some local languages and terms appear, such as Rojo Koyo, Sathu Galak, and Celathu. From the aspect of vernacular, it can be said that Tafsir al-Ibriz describes the social context of Javanese Islam well at the time when this interpretation of the Qur'an was written.